2016
DOI: 10.1186/s13068-016-0542-x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced lipid production by Rhodosporidium toruloides using different fed-batch feeding strategies with lignocellulosic hydrolysate as the sole carbon source

Abstract: BackgroundIndustrial biotechnology that is able to provide environmentally friendly bio-based products has attracted more attention in replacing petroleum-based industries. Currently, most of the carbon sources used for fermentation-based bioprocesses are obtained from agricultural commodities that are used as foodstuff for human beings. Lignocellulose-derived sugars as the non-food, green, and sustainable alternative carbon sources have great potential to avoid this dilemma for producing the renewable, bio-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 128 publications
(76 citation statements)
references
References 52 publications
3
68
0
2
Order By: Relevance
“…Only a few focus on other types of challenges such as the inhibitor management with respect to some of the substrates that are used for the production of lipids. Due to the limitation of substrate variation, it is necessary to adapt, modify, and develop strains with the aim of improving the utilization of different sugars in hydrolysates obtained from lignocellulosic biomass, as well increasing the tolerance to inhibitory compounds present in them . In this regard, synthetic biology and bioengineering are essential tools to improve the production and adaptation capacities that this strain presents .…”
Section: Challenges In Lipid Production In Rhodosporidium Genrementioning
confidence: 99%
See 1 more Smart Citation
“…Only a few focus on other types of challenges such as the inhibitor management with respect to some of the substrates that are used for the production of lipids. Due to the limitation of substrate variation, it is necessary to adapt, modify, and develop strains with the aim of improving the utilization of different sugars in hydrolysates obtained from lignocellulosic biomass, as well increasing the tolerance to inhibitory compounds present in them . In this regard, synthetic biology and bioengineering are essential tools to improve the production and adaptation capacities that this strain presents .…”
Section: Challenges In Lipid Production In Rhodosporidium Genrementioning
confidence: 99%
“…To reduce these feedstock costs, different carbohydrates have been obtained from lignocellulosic biomass from forestry residues . Various studies in the literature have reported the use of different culture media, such as glucose, xylose, crude glycerol, acetic acid, sugarcane juice, and hydrolysates from different kinds of lignocellulosic biomass as well as different cultivation systems (flask, batch, fed, fed‐batch, and pilot) .…”
Section: Introductionmentioning
confidence: 99%
“…These IBR designs are chosen as representative examples of biorefineries co‐producing fuels and chemical products. The carbohydrate‐to‐hydrocarbon processes in these IBR designs reflect experimental work focused on oleaginous yeast fermentation at the National Renewable Energy Laboratory, with the ultimate objective to produce fungible drop‐in hydrocarbon biofuels, as one research and development strategy pursued experimentally . The co‐products evaluated here are potential platform chemicals of interest to the bioenergy industry.…”
Section: Methodsmentioning
confidence: 99%
“…The carbohydrate-to-hydrocarbon processes in these IBR designs reflect experimental work focused on oleaginous yeast fermentation at the National Renewable Energy Laboratory, with the ultimate objective to produce fungible drop-in hydrocarbon biofuels, 3,30,32 as one research and development strategy pursued experimentally. 33 The co-products evaluated here are potential platform chemicals of interest to the bioenergy industry. Succinic acid was initially identified as a top value-added chemical from sugar focused routes in a 2004 Department of Energy-led study.…”
Section: Integrated Biorefinery Designsmentioning
confidence: 99%
“…R. toruloides is also an attractive host for production of sustainable chemicals and fuels from low-cost lignocellulosic feedstocks. Wild isolates of R. toruloides can produce lipids and carotenoids from a wide variety of carbon sources including glucose (19, 20), xylose (11), and acetate (21), as well as complex biomass hydrolysates (22). They are also relatively tolerant to many forms of stress including osmotic stress (23) and common inhibitors found in hydrolysates produced by common biomass deconstruction technologies, such as dilute acid pretreatment followed by enzymatic saccharification (24, 25).…”
Section: Introductionmentioning
confidence: 99%